Pengaruh Citra Merek, Pengetahuan Produk, dan Label Halal Terhadap Keputusan Pembelian Mie Gacoan - Firyal Eltama, Naura; Sriminarti, Nurul (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of brand image, product knowledge, and halal labeling on the purchasing decisions of Mie Gacoan consumers in the South Tangerang area. The research employs a quantitative approach involving 150 respondents, with data collected through questionnaires. The respondent criteria include individuals aged 15–29 years who have purchased Mie Gacoan products at least three times per month. The collected data were tabulated and analyzed using the Statistical Package for the Social Sciences (SPSS) with multiple linear regression analysis. The results indicate that brand image (X1) has a positive but not significant effect on consumers’ purchasing decisions. Meanwhile, product knowledge (X2) and halal labeling (X3) each have a positive and significant effect on purchasing decisions.